The Master’s Tools will never Dismantle the Master’s House": Some Meditations on Women, Culture, and Politics - Ruiz, Lester Edwin J. (Silliman Journal, 2022)
Feminist struggles are illustrative of what "becoming a people" entails. As theory and practice, they problematize, coventional notions of political identity in the modern world, providing the grounds for challenging the historically-specific, and often invisible, male-centric accounts of political identity. They are cultures of resistance and solidarity, deconstructing, on the one hand, male-centric, technostrategic discourses, militarized and decontextualized rationalities, and on the other hand , articulating compelling alternative visions of possible futures including alternative conceptions of rationality and imagination. Finally, they are practices of cultural transformation that are aimed at eradicating structures and processes of domination, articulating different understandings of community and identity, describing and delineating , the full range of women's experiences - which can shape and transform the male-centric, hierarchical, often mysoginist practices in social and political life.